A Survey of Blind Orientation and Mobility Specialists about the Accommodations and Teaching Strategies They Use When Providing Orientation and Mobility Services. (May 2021) - Griffin-Shirley, Nora; Bozeman, Laura; Nguyen, The; Othuon, Vitalis; Page, Anita; Hahm, Juhyun; Hahm, Juyoung; Lee, Jaehoon
Introduction: The purpose of the study was to survey orientation and mobility (O&M) instructors who are blind concerning the identification of accommodations, teaching techniques, and resources to teach students with visual impairments (i.e., blindness or low vision). Methods: The study utilized an online survey via Qualtrics (2019) with 27 closed- and open-ended items to identify accommodations, teaching techniques, and resources needed. The survey was e-mailed to membership and certification organizations requesting O&M instructors who are blind to participate for 12 weeks. The participants were 15 O&M specialists, mostly male and Caucasian. Survey data were then analyzed using descriptive statistics. Results: Forty percent of the participants reported that there were minimal standards that they had to demonstrate prior to their admittance into an O&M program. About one-fourth of the participants mentioned their program was modified because of their visual impairment. Eleven participants (73%) reported that their nonvisual instructional strategies and techniques were predominantly gained through their university programs or other visually impaired instructors (27%, n = 4). Discussion: Aspects of this study that are similar to the current literature are smaller faculty-to-student ratios for blindfold or simulation cane courses, accommodations used by participants, and suggestions for monitoring the safety of students. The results revealed the participants' strong belief in the importance of immersion training, the use of the Structured Discovery Cane Travel (SDCT), nonvisual skills during O&M instruction, sleep shades, and students' problem-solving abilities. Implication for practitioners: Although the participants had received SDCT immersion training, most personnel preparation programs approved by the Association for the Education and Rehabilitation of Blind and Visually Impaired do not use this method. For this reason, it is important for faculty to identify best teaching practices from among all programs and to integrate these practices into their curricula. Sharing best practices could strengthen all programs. Moreover, students with visual impairments should be taught early about self-advocacy and the ability to have helpful knowledge about one's skills at a university and in the workplace.